Photothermal affects our live - Zakaria, Azmi (Universiti Putra Malaysia Press, 2013)
The photothermal effect of solid was first discovered by Alexander Graham Bell in 1880 while its application on determining the type of gaseous was recognized in 1903. However the application on solid only began in 1973 after Parker discovered it accidently during the characterizing of gas with photoacoustic cell. Following this, the research activities on solid have exploded by its flexibility in photothermal detections and can be applied in various applications. Here the review on photothermal research activities on sample characterizing in UPM and others are presented. Also included are the future direction and challenges in photothermal research.